Analysing on influencing factors of students’ career choice using Fuzzy Analytic Hierarchy Process (FAHP) / Salsabila Saimuddi and Khairu Azlan Abd Aziz - Saimuddi, Salsabila; Abd Aziz, Khairu Azlan (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The number of professions available to students has grown over time, making it more difficult for them to choose a career after finishing their studies. The study examined the factors that have the greatest influence on students' career choices to assist them in making that decision. The aim is to identify the main factor and rank the main factor and subfactor that influence students’ career choices using fuzzy Analytic Hierarchy Process (AHP). A questionnaire was distributed to collect data for the study using Classic Saaty’s Scale. Based on the value collected, the study implemented a fuzzy analytic hierarchy process (AHP) to identify the main factor influencing students’ career choices and rank the main factor and sub-factor that influence students’ career choices. To identify the main factors, factors with a normalized weight that have the highest value are the factors that most influence students’ career choices. To rank factors and sub-factors, the ranking went from the highest normalized weight to the lowest normalized weight. In the results, the main factor that most influences students’ career choices are the personal interest factor, which has the highest normalized weight. In ranking the factors influencing students’ career choices, experts agree that personal interest is the most influential factor. For sub-factors, the workplace is the most influential factor in students' career choices, while the sub factor with the least influence is safety under the parental factor, which is also the least ranked of the factors influencing students' career choices.